Contribution Contribution of Sharia Securities Crowdfunding to a Sustainable Economy (Case Study: Shafiq Sharia Securities Crowdfunding) - Putri Adila; Muhammad Ikhsan Harahap; Purnama Ramadani Silalahi (Indonesian Journal Publisher, 2024)
This research aims to analyze the contribution of Sharia Securities Crowdfunding (SCF) to a sustainable economy. In this research, the SCF Shafiq platform is considered as an example of a case study. The method used is descriptive with a qualitative approach. The research results show that the development of SCF Syariah has developed very rapidly. The SCF Syariah platform has developed to serve customers in various sectors, such as investree in the retail, iGrow in the agricultural sector, Ethiscrowd in the housing and property sector, and others. In 2023, there will be 16 Securities Crowdfunding (SCF) organizers who have obtained permission from the Financial Services Authority (OJK). The SCF Sharia platform registered with the OJK has distributed 77 billion rupiah in 2018, while the potential for sharia crowdfunding reaches 5-7 trillion transactions per year. Sharia crowdfunding transactions are growing at 16.3% per year. In this research, several obstacles that are often faced in the implementation and development of Sharia SCF are also noted, such as differences in sharia interpretation and technical problems. However, this research shows that the development of Sharia SCF can improve the community's economy and become an alternative capital solution for SMEs.